المرافقة المقاولاتية كآلية فعالة لدعم المؤسسات الصغيرة والمتوسطة لدى خريجي الجامعات (Journal of Economics and Management Research, 2021)
نسعى من خلال هذه الدراسة إلى تسليط الضوء على أحد أهم الأساليب التي تساعد على إنشاء واستمرار المؤسسات الصغيرة والمتوسطة لدى الطالب الجامعي ألا وهو أسلوب المرافقة المقاولاتية، وإلى تبيان مدى أهميته ودوره الفعال في التخفيف من حدة الصعوبات التي تحول دون بقاء هذه المؤسسات، باعتباره المشجع على خلق بيئة عمل ملائمة لتطويرها، فمن خلال هذا تم التعرف على مفهوم المرافقة المقاولاتية والمؤسسات الصغيرة والمتوسطة وتقديم مختلف هيئات الدعم المساعدة على إنشائها. In This study, we aim to highlight one of the most important methods that help to establish and sustain small and medium enterprises, namely, the method of business accompaniment, to indicate its importance and its effective role in alleviating the difficulties that prevent the survival of these institutions and encourage the creation of a suitable environment for their development. , By identifying the concept of business accompaniment and small and medium enterprises and providing various support bodies to help establish them.